Synchronized sorcery - Blackwell, Juliet (Blackwell, Juliet. Witchcraft mystery series., 2021)
"Strange things are happening in Lily Ivory's San Francisco. First, she finds a vintage mermaid costume which dates from the 1939 San Francisco's Treasure Island World's Fair...Next, she stumbles upon a dead man in the office of her predecessor...When the dead man is linked to the mysterious mermaid costume, and then yet another victim is found...Lily uncovers ties between the long-ago World's fair and the current murders, and begins to wonder whether the killer might be hiding in plain sight"--